As representações sociais dos acadêmicos de enfermagem e fonoaudiologia sobre o processo de envelhecimento e a formação para o cuidado ao idoso - Mendes, Juliana (2015)
Introduction. The progressive increase of longevity in the global context shows the relevance for the development of studies to deepen the understanding on the process of human aging, as well as the improvement in professionals’ qualification to work in the elderly population’s healthcare. Elderly healthcare demands the engagement of qualified professionals from different areas of knowledge, among those, nurses and speech language pathologists, who are the focus on this study. Objective. To analyze nursing and speech language pathology undergraduates’ social representations on the aging process and education for elderly healthcare. Methodological trajectory. Qualitative research grounded in Moscovici’s Social Representation Theory. Twenty- five nursing and speech language pathology undergraduates from two public universities and two private ones, located in the capital city and interior of Paraná State, participated in the study. Students’ inclusion criterion was to be attending the 8th period of Nursing or Speech Language Pathology courses. For data collection, thematic interview was used, comprising digitally-recorded open questions. The interviews were held in the universities, complying with a schedule set up with the responsible professors for the 8th period undergraduates. In each of the investigation settings, a proper classroom was reserved, which provided the private environment for carrying out the interviews, involving only the researcher and the participant. Data collection was held between June 15th, 2012 and January 15th, 2013, being organized according to Lefèvre and Lefèvre’s Discourse of the Collective Subject. The discourse of the collective subject is a technique of organization and analysis for qualitative data, verbal in nature, obtained by means of accounts. For the construction of the Discourse of the Collective Subject, four methodological figures are used: anchoring, central idea, key-expressions and the elaboration of the discourse of the collective subject. Legal and ethical principles were complied in this study by means of the approval for the Ethics Research Committee of the University responsible for the project, protocol n. 04130612.2.0000.0096. Results. The twenty-five participants in the study feature mean age of 27.8, with 24 being female. The social representations which emerged from the undergraduates’ interviews enabled the organization of two themes, six central ideas and six anchors: Theme 1 – knowledge on aging in graduation. Anchoring: aging theme is superficially addressed in graduation curricula. Central idea B: theoretical approaches on aging during graduation. Anchoring: theoretical knowledge prioritizes biologicist aging. Theme 2 - Elderly healthcare practice in graduation. Central idea A: lived experiences in elderly healthcare academic training. Anchoring: older people need physical decay-related healthcare. Central idea B: undergraduates’ perception on the elderly in the academic practice. Anchoring: Elderly people are denied their power of decision. Central idea C: negative feelings involving elderly healthcare. Anchoring: infantilization of old age. Central idea D: positive feelings involving elderly health care. Anchoring: reciprocity in caregiver and cared subject’s relation. Final Considerations: It is perceived that the two investigated graduation teaching, on elderly healthcare is incipient. Discipline content founded on the Cartesian model tends to fragment care. Consequently, healthcare practices turn to physical decay. Elderly infantilization and constraints to their power of decision are also daily evidenced. It is pointed out that undergraduates perceive, due to their practical activities experienced in graduation, a reciprocity relation between the caregiver and the subject being cared. The need to include specific disciplines for the elderly humanized care is imperative, because only the education of qualified human resources may care and assist the aging population providing them whole healthcare.